Asymmetric synthesis of (R)-hexane-1,5-diol, (R)-hex-3-ene-1,5-diol and (R)-6-methylhept-5-en-2-ol (sulcatol) employing a tandem asymmetric conjugate addition and stereospecific Meisenheimer rearrangement protocol - Davies, S; Smyth, G (1996)
Highly stereoselective conjugate addition of lithium (R)-N-methyl-(α-methylbenzyl)amide to tert-butyl (E,E)-hexa-2,4-dienoate, followed by reduction of the ester to the corresponding alcohol, affords a substrate which undergoes, upon oxidation, a stereospecific Meisenheimer rearrangement to give a single diastereomer of the corresponding trialkylhydroxylamine. The analogous N-benzyl adduct gives lower yields in the oxidation-rearrangement reaction. If the ester is not reduced to the alcohol, N-oxidation leads to Cope elimination, not Meisenheimer rearrangement. Cleavage of the N-O bond gives (R)-hex-3-ene-1,5-diol, and hydrogenation of the double bond affords (R)-hexane-1,5-diol in high ee. This methodology has been applied to the synthesis of the insect pheromone (R)-6-methylhept-5-en-2-ol (sulcatol) from tert-butyl (E,E)-hexa-2,4-dienoate, via a sequence involving conjugate addition of the lithium amide, Grignard addition to the ester, Meisenheimer rearrangement, hydrogenation of the double bond, dehydration of the tertiary alcohol and finally N-O bond cleavage.